Cover Feature: Microwave‐Assisted Decarbonylation of Biomass‐Derived Aldehydes using Pd‐Doped Hydrotalcites (ChemSusChem 2/2020). Issue 2 (20th January 2020) - An, Nan; Ainembabazi, Diana; Reid, Christopher; Samudrala, Kavya; Wilson, Karen; Lee, Adam F.; Voutchkova‐Kostal, Adelina
Abstract : The Cover Feature shows the atom‐ and energy‐efficient continuous production of biomass‐derived platform chemicals over Pd/hydrotalcite bifunctional catalysts. More information can be found in the Full Paper by N. An et al on page 312 in Issue 2, 2020 (DOI: 10.1002/cssc.201901934 ).